The Effect of The Non-Physical Work Environment and Career Development on Turnover Intention With Job Satisfaction Mediation Work on PT. Yoshioka Indonesia - Deddy Novie Citra Arta (Cita Konsultindo Research Center, 2022)
PT. Yoshioka Indonesia has a reasonably high turnover intention rate, which causes the company's productivity to decrease with increasing consumer complaints from observations due to several things, such as non-physical work environment, career development, and low employee job satisfaction, which makes turnover intention at PT. Yoshioka Indonesia is relatively high, so PT. Yoshioka Indonesia lacks potential employees. The type of approach used is quantitative. This study took a population of employees of PT. Yoshioka Indonesia and sampling using a saturated sample technique with 97 respondents. Data collection includes observation and distributing questionnaires with the help of the Smart PLS 3.3.3 program. The results obtained that the non-physical work environment has no effect and is not significant on turnover intention with the original sample value of 0.042 with a T statistic value of 0.479 and P Values of 0.632 or greater than the value of (0.632 <0.05), career development has a negative and significant effect on turnover intention with the original sample value of 0.449 with a T-statistical value of 3.469 and P Values of 0.001 or less than the value of (0.001 <0.05), job satisfaction has a negative and significant effect on turnover intention, intention with the original sample value of 0.484 with a T statistic of 4.370 and P Values of 0.000 or less than the value of (0.000 <0.05) non-physical work environment has a negative and significant impact on turnover intention through mediation of job satisfaction, work with sample values original value of 0.222 with a T-Statistic value of 2.593 and P Values of 0.010 or less l of the value of (0.010 <0.05), and career development has a negative and significant effect on turnover intention through job satisfaction mediation with the original sample value of 0.233 with a T statistic value of 2.745 and P Values of 0.006 or less than the value of ( 0.006<0.05).